Endosomal toll‐like receptors play a key role in activation of primary human monocytes by cowpea mosaic virus. Issue 2 (15th November 2019) - Albakri, Marwah M.; Veliz, Frank A.; Fiering, Steven N.; Steinmetz, Nicole F.; Sieg, Scott F.
Summary: The plant virus, cowpea mosaic virus (CPMV), has demonstrated a remarkable capacity to induce anti‐tumour immune responses following direct administration into solid tumours. The molecular pathways that account for these effects and the capacity of CPMV to activate human cells are not well defined. Here, we examine the ability of CPMV particles to activate human monocytes, dendritic cells (DCs) and macrophages. Monocytes in peripheral blood mononuclear cell cultures and purified CD14+ monocytes were readily activated by CPMV in vitro, leading to induction of HLA‐DR, CD86, PD‐L1, IL‐15R and CXCL10 expression. Monocytes released chemokines, CXCL10, MIP‐1α and MIP‐1β into cell culture supernatants after incubation with CPMV. DC subsets (pDC and mDC) and monocyte‐derived macrophages also demonstrated evidence of activation after incubation with CPMV. Inhibitors of spleen tyrosine kinase (SYK), endocytosis or endocytic acidification impaired the capacity of CPMV to activate monocytes. Furthermore, CPMV activation of monocytes was partially blocked by a TLR7/8 antagonist. These data demonstrate that CPMV activates human monocytes in a manner dependent on SYK signalling, endosomal acidification and with an important contribution from TLR7/8 recognition. Abstract : Cowpea mosaic virus (CPMV) is a plant virus that has been previously shown to induce potent anti‐tumour immune responses in mice when injected into tumours. The present study demonstrates that CPMV can mediate activation of primary human professional antigen‐presenting cells, including monocytes, dendritic cells and macrophages. CPMV‐mediated activation of human monocytes is blocked by inhibition of endosomal TLR7/8 and spleen tyrosine kinase.